VD_FINDINFO Arrêt / 2023 / 172 vom 13. April 2023 - VD Tribunal cantonal (2023)
DÉLAI DE CARENCE D'UNE ANNÉE, ÉVALUATION DE L'INVALIDITÉ, REVENU SANS INVALIDITÉ, REVENU D'INVALIDE | 28 al. 1 let. b LAI, 16 LPGA